A simple method to monitor performance of forced vital capacity - Volta, C. A; Ploysongsang, Y; Eltayara, L; Šulc, Jan; Milic-Emili, J (Journal of applied physiology (1985), 1996)
The forced vital capacity (FVC) maneuver is the most common lung function test. One of its major prerequisites is that it be performed with sufficient effort to achieve the maximal flows that are due to expiratory flow limitation. To verify this, in nine normal subjects, short (0.25-s) pulses of negative pressure (-5 to -20 cmH2O) were applied at the mouth at different times (0.25-1 s) after the onset of 1) FVC maneuvers and 2) vital capacity expirations with submaximal expiratory efforts (SVC). All subjects were experienced in FVC maneuvers. With FVC, the expiratory flow did not change with application and removal of negative-pressure pulses, apart from brief flow transients, mainly reflecting displacement of air from the compliant oral and neck structures. With SVC, flow increased throughout the application of the negative-pressure pulses. Thus application of pulses of negative pressure provides a simple method for on-line recognition of whether an FVC maneuver is performed with sufficient effort to achieve flow limitation.
Keywords: vitální kapacita; Adult; Peak Expiratory Flow Rate; Exercise; ventilátory s negativním tlakem; Respiratory Function Tests; dospělí; respirační funkční testy; Forced Expiratory Volume; Vital Capacity; mužské pohlaví; cvičení; Ventilators, Negative-Pressure; Humans; lidé; vrcholová exspirační průtoková rychlost; usilovný výdechový objem; Male